Information technology tools - Arora, Ashok; Bansal, Shefali (New Delhi : Pentagon press, 2004)
Information Technology Tools and Applications is primarily written in response to the dearth of quality texts on Information Technology (IT) tailored to serve the needs of on-site and distance learners. It introduces tertiary level students to the fundamentals of IT tools and their applications in very simple and lucid language. The content includes: vivid description of basic ICT concepts - computer hardware and software (particularly those for performing data processing tasks as word processing, spreadsheet, database management and presentations), description of web browsing and communication, as well as the social and health impacts of ICT use. An expose on legal and security issues relating in IT use and the digital divide question was also presented. Presentation of concepts is simplified both by the use of non-technical language and illustrations to aid comprehension. The book is thus suitable for undergraduate and postgraduate students in communication, computer science, library and information science, information and knowledge management in universities and polytechnics where a basic grounding of IT is taught.IT teachers will equally find it invaluable.
Includes bibliography and index.
Keywords: Multi media; Information techology